Predicting the impacts of palm heart and fruit harvesting using Integral Projection Models - Mendes, Eduardo; Galdino, Felippe; Portela, Rita de C. Q. (Frontiers in Forests and Global Change, 2022)
Due to increasing human impact on natural resources, we assessed the harvesting of non- timber forest products to verify demographic changes in populations of a native palm tree. Euterpe edulis is native to the Atlantic Forest in Brazil, characterized by high deforestation and fragmentation. This palm is also targeted for palm heart and fruit harvesting. The threats posed by such factors motivated this study, as they might lead to the decrease of natural populations. The viability of sustainably harvesting the species in small fragmented areas is unknown. We performed simulations for palm heart and fruit harvesting in three small populations (SH, AJ and ES) sampled in a one-year interval (2010 – 2011) to verify whether these practices are sustainable. Different harvesting scenarios were simulated: (1) no harvesting; (2) harvesting of palm heart of mature individuals (presenting reproductive structures); (3) harvesting of palm heart of large individuals (diameter at ground level > 65 mm); (4) harvesting of fruits. Each scenario was simulated at different harvesting intensities (% of individuals or fruits harvested). Integral Projection Models were used to calculate two demographic parameters: population growth rate (λ) and elasticity. In the no harvesting scenario, the populations had λ > 1 (SH = 1.0655, AJ = 1.0184, and ES = 1.0862). Palm heart harvesting proved to be sustainable in both scenarios, but at higher intensity in scenario (2) (SH = 83%, AJ = 14%, ES = 35%) than in scenario (3) (SH = 17%, AJ = 4%, ES = 16%). Fruit harvesting was sustainable at any intensity for all three populations. Because the survival of large individuals has high impact on λ, palm heart harvesting was in most cases sustainable only at low intensities. On the other hand, as fecundity and seedling survival have low impact on λ, fruit harvesting still proved sustainable at high intensities. Although the populations are tolerant to harvesting to some degree, it must be conducted carefully. As populations are fragile due to the current condition of reduced population size, the removal of palms at any rate can affect population persistence and generate possible cascade effects on the forest.